2015
DOI: 10.1111/ggi.12682
|View full text |Cite
|
Sign up to set email alerts
|

Aging well: Processing speed inhibition and working memory related to balance and aerobic endurance

Abstract: Better dynamic balance and aerobic endurance predicted enhanced processing speed, inhibition and working memory in older adults, with these last two domains considered components of executive function. Geriatr Gerontol Int 2017; 17: 108-115.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Behavioral studies have also reported positive relationships between aging and physical exercise. For example, aerobic and balance training predicted enhanced processing speed, inhibition and working memory [54]. Older adults with an active life-style performed better on working memory, spatial memory, inhibition capacity, and the ability to switch between tasks [35].…”
Section: The Role Of Physical Exercise In Successful Agingmentioning
confidence: 99%
“…Behavioral studies have also reported positive relationships between aging and physical exercise. For example, aerobic and balance training predicted enhanced processing speed, inhibition and working memory [54]. Older adults with an active life-style performed better on working memory, spatial memory, inhibition capacity, and the ability to switch between tasks [35].…”
Section: The Role Of Physical Exercise In Successful Agingmentioning
confidence: 99%
“…Aerobic exercise [ 19 22 ] and resistance exercise [ 11 , 23 ], both separately and in combination [ 9 , 20 ], can improve cognition in older persons. Additionally, aerobic and balance exercises link to executive function, a component of cognition [ 24 ]. Likewise, coordination exercise can improve cognition in older persons [ 25 27 ], appearing to involve in perceptual speed and visual-spatial network [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise and physical activity may potentially have positive benefit on cognitive function. Observational studies have suggested there may be an interplay between motor and cogni-tive processes, as balance ability and functional ambulatory capacity were positively associated with processing speed, response inhibition and working memory in older adults (1) and the Timed Up and Go test, a measure of functional walking and balance, was an independent predictor cognitive decline after first ischemic stroke (2). In prospective trials, resistance training contributed to improved executive functions in older adults (3), and aerobic training led to increased hippocampal volume and improved verbal memory and learning (4), and spatial memory (5).…”
Section: Introductionmentioning
confidence: 99%